Enzyme stereospecificity as a powerful tool in searching for new enzymes - Skarydová, Lucie; Skarka, Adam; Solich, Petr; Wsól, Vladimír (Current drug metabolism, 2010)
Chirality is a ubiquitous feature present in all biological systems that plays a very important role in many processes. Drug metabolism is one of these and is the subject of this review. Chiral drugs can be metabolized without changes in their chiral characteristics, but also their biotransformation may give rise to a new chiral center. On the other hand, prochiral drugs are always metabolized to chiral metabolites. The ratio of formed enantiomers/diastereoisomers is the constant known as enzyme stereospecificity, and this is as important a characteristic for each enzyme-substrate pair as is the Michaelis constant. Drugs are often substrates for multiple biotransformation enzymes, and all enzymes involved may metabolize a chiral or prochiral drug with different stereospecificity so that variant enantiomer ratios are achieved. Enzyme stereospecificity of whole cell fraction is the sum of the stereospecificities of all enzymes participating in metabolism of a substrate. Differing stereospecificities in the metabolism of a drug between whole cell fraction and enzymes point to the contribution of other enzymes. Using several drugs as examples, this review shows that enzyme stereospecificity can serve as a powerful tool in searching for new biotransformation enzymes. Although it is not often used in this way, it is clear that this is possible. There are today drugs with well-known chiral metabolism, but, inasmuch as many xenobiotics are poorly characterized in terms of chiral metabolism, enzyme stereospecificity could be widely utilized in researching such substances.
Keywords: Substrate Specificity; sekvence aminokyselin; molekulární sekvence - údaje; Animals; lidé; Biotransformation; Molecular Sequence Data; Stereoisomerism; léčivé přípravky; jaterní mikrozomy; biotransformace; substrátová specifita; Humans; Amino Acid Sequence; zvířata; Microsomes, Liver; Pharmaceutical Preparations; stereoizomerie